1997
DOI: 10.1007/bf00176881
|View full text |Cite
|
Sign up to set email alerts
|

Long-term evaluation of primary anterior chamber intraocular lens implantation in complicated cataract surgery

Abstract: The long-term visual outcome and complications related to the use of a semiflexible open-loop alI-PMMA anterior chamber intraocular lens were evaluated in 40 eyes in which the capsular support was lost. The mean follow up time was 2.3 years (range 6 months to 6.7 years). 55% of the eyes had exfoliation syndrome. 68% (27 of 40 eyes) obtained a visual acuity of 0.5 or better, and only in one of the remaining eyes decreased visual acuity was related to cataract surgery (cystoid macular oedema). No cases of cornea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…There are four options for IOL implantation in aphakic eyes with inadequate capsular support: 1 (1) An open-loop AC-IOL, 2, 3, 4 (2) a scleral-sutured PC-IOL, 5, 6, 7 (3) an iris-sutured PC-IOL, 8, 9, 10 and (4) a scleral-sutured modified capsular tension ring. 11, 12, 13, 14 AC-IOLs have been improved from a closed-loop design to an open-loop design, and the open-loop AC-IOLs have been shown to be less traumatic to corneal endothelial cells than are closed-loop AC-IOLs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are four options for IOL implantation in aphakic eyes with inadequate capsular support: 1 (1) An open-loop AC-IOL, 2, 3, 4 (2) a scleral-sutured PC-IOL, 5, 6, 7 (3) an iris-sutured PC-IOL, 8, 9, 10 and (4) a scleral-sutured modified capsular tension ring. 11, 12, 13, 14 AC-IOLs have been improved from a closed-loop design to an open-loop design, and the open-loop AC-IOLs have been shown to be less traumatic to corneal endothelial cells than are closed-loop AC-IOLs.…”
Section: Discussionmentioning
confidence: 99%
“…11, 12, 13, 14 AC-IOLs have been improved from a closed-loop design to an open-loop design, and the open-loop AC-IOLs have been shown to be less traumatic to corneal endothelial cells than are closed-loop AC-IOLs. 3, 4 However, studies have shown that corneal edema with open-loop AC-IOLs occurs more frequently than with scleral-sutured or iris-sutured PC-IOLs, and that glaucoma escalation occurs at an incidence of between 1.3 and 15%. 1, 2, 3 Thus, such complications to the angle may be unavoidable with the AC-IOL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have however demonstrated how the onset of cystoid macular edema varies from 6.7% to 42.9% following scleral-fixated IOL implants while it is drastically reduced from 5.7% to 22.2% with 4 ISRN Ophthalmology anterior chamber IOL implants [11,19,[30][31][32][33][34][35]. Thus the laser flare meter data we collected in this study, highlight that, following secondary IOL implantation, due to the absence of capsular support, there is a subclinical inflammation that is still present three months after surgery and is statistically significant when compared with flare values of patients undergoing phacoemulsification and contemporary IOL implantation in the capsular bag.…”
Section: Discussionmentioning
confidence: 99%